La crítica en la enseñanza de las ciencias: constructivismo y contradicción - Laburu, C. E. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1996)
In this study we try to justify the importance of considering in science teaching that facet of critical thinking that is based on the idea of comparing the evidence with the prevision. Together with critical thinking, the most general and fundamental condition of coherent thinking must prevail. This viewpoint is justified by employing the popperian epistemological model, the cognitive model by Piaget and the model of conceptual change. We show that for these models, contradiction is an essential epistemological element. We suggest that critical thinking should be the principal object of teachers in the science class.